1989
DOI: 10.1002/jcp.1041400308
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric distribution of phospholipids in the membrane of vesicles released during in vitro maturation of guinea pig reticulocytes: Evidence precluding a role for “aminophospholipid translocase”

Abstract: Guinea pig reticulocytes lose their transferrin (Tf) binding activity during maturation, in the form of vesicles (exosomes) released into the extracellular medium. Vesicles were prepared from cultures of reticulocytes to study the possible externalization of a particular membrane-associated activity, i.e., that of "aminophospholipid translocase." Analysis of the peptide composition of these vesicles revealed that the major proteins are the Tf receptor and another peptide (70kDa), which is probably the "clathri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 36 publications
(46 reference statements)
4
101
0
3
Order By: Relevance
“…To ensure that the materials recovered at D2, D4, and D7 all corresponded to bona fide exosomes, we compared the morphology and physical characteristics of the different preparations with several complementary approaches as follows: electron microscopy, fluorescence anisotropy, and sedimentation on sucrose gradients. At all three time points, the materials recovered were composed of typical vesicles with the expected aspect and size for exosomes (34) as observed on transmission electron microscopy images (Fig. 3A).…”
Section: Resultssupporting
confidence: 58%
“…To ensure that the materials recovered at D2, D4, and D7 all corresponded to bona fide exosomes, we compared the morphology and physical characteristics of the different preparations with several complementary approaches as follows: electron microscopy, fluorescence anisotropy, and sedimentation on sucrose gradients. At all three time points, the materials recovered were composed of typical vesicles with the expected aspect and size for exosomes (34) as observed on transmission electron microscopy images (Fig. 3A).…”
Section: Resultssupporting
confidence: 58%
“…10,35,36 We previously reported that reticulocyte exosomes freshly collected following in vitro maturation presented a normal membrane asymmetry. 37 However in the same study, we demonstrated the absence of the aminophospholipid translocase in reticulocyte exosomes, suggesting that the phospholipid asymmetry should be progressively lost with time, leading to PS exposure on the membrane outer leaflet. It is worth noting that accordingly, the presence of aminophospholipids on the surface of exosomes has been reported in some cases 38,39 and that MFG-E8 has been described as associated with exosomes secreted by various cells.…”
Section: Discussionmentioning
confidence: 57%
“…The distributions are plotted also for the hypothetical cases that: (i) the critical mole fraction interval would be 1͞8 (thin continuous line) or (ii) 1͞10 (dashed line) instead of the model predicted value of 1͞9, or (iii) that no preferred compositions would exist, i.e., the concentration of PE could obtain any value between the experimental extremes 22.2 mol % (cat) and 35.9 mol % (buffalo) with equal probability (horizontal dotted line). The head group class distributions were calculated from published data (27)(28)(29)(30)(31)(32). Unidentified lipids, present in sheep, camel, and goat erythrocytes (4.8, 3.4, and 0.8 mol %, respectively), were excluded from the analysis, and the percentages of the other lipids were corrected accordingly to add to 100%.…”
Section: ϫ8mentioning
confidence: 99%